Scheduling Jobs on Two Facilities to Minimize Makespan - Bulfin, R. L.; Parker, R. G. (Management Science, 1980)
This paper is concerned with the problem of scheduling tasks on a system consisting of two parallel processors in order that makespan be minimized. In particular, we treat a variety of modifications to this basic theme, including the cases of identical, proportional, and unrelated processors. In addition, a heuristic scheme is suggested when precedence constraints exist where such constraints may be assignment dependent. Substantial computational experience is reported in all cases where it would appear that relatively large problems can be handled routinely.